Asymptotic study of supercritical surface Quasi-Geostrophic equation in critical space. (November 2022) - Benameur, Jamel; Katar, Chaala
Abstract: In this paper we prove, if θ ∈ C ( [ 0, ∞ ), H 2 − 2 α ( R 2 ) ) is a global solution of supercritical surface Quasi-Geostrophic equation with small initial data, then ‖ θ ( t ) ‖ H 2 − 2 α decays to zero as time goes to infinity. Fourier analysis and standard techniques are used.